Darna as Canonical Counter-Discourse on Power in the Superhero Genre - Brillon, Cherish Aileen A. (Humanities Diliman: A Philippine Journal of Humanities, 2023)
Power is an important iconography in the superhero genre. In this regard, one of the most recognizable iconographies in Darna is the bato (stone). However, the nature of Darna’s powers and the constitution of the stone are rarely discussed when talking about her even if these are important elements in her overall mythology. To address this, the paper explores the materiality of Darna’s powers, specifically the origin and constitution of the stone, and situates it within a Filipino belief system and folk culture. Specifically, it traces the roots of Darna’s powers in agimat or anting-anting (amulets or talismans), sapi (spirit possession), and loob (pure heart) as these are elements that give her a distinct Filipino identity. This articulation of Darna’s power is based on the idea of canonical counter-discourse where assumptions about canon texts in fiction are subverted for post-colonial purposes. In discussing Darna’s power, this paper not only affirms the Filipino folk culture origins of Darna, but also subverts the idea of power in the Western superhero genre which remains very male-centric, continues to be associated with masculine expressions of power, and privileges the individual over the collective.